2022
DOI: 10.7554/elife.82411
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine synthetase mRNA releases sRNA from its 3′UTR to regulate carbon/nitrogen metabolic balance in Enterobacteriaceae

Abstract: Glutamine synthetase (GS) is the key enzyme of nitrogen assimilation induced under nitrogen limiting conditions. The carbon skeleton of glutamate and glutamine, 2-oxoglutarate, is supplied from the TCA cycle, but how this metabolic flow is controlled in response to nitrogen availability remains unknown. We show that the expression of the E1o component of 2-oxoglutarate dehydrogenase, SucA, is repressed under nitrogen limitation in Salmonella enterica and E coli. The repression is exerted at the post-transcript… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…This is exemplified by GlnZ whose expression is activated by NtrC and is thus a member of the NtrC regulon. The regulatory targets of GlnZ have been explored in a number of previous studies (50,51), and many of those identified previously have also been identified in the currently study (Figure S3A). However, our data additionally uncovered that GlnZ interacts with the mRNA of nac in the N-growth state, which encodes a global transcription factor and is a member of the NtrC regulon.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This is exemplified by GlnZ whose expression is activated by NtrC and is thus a member of the NtrC regulon. The regulatory targets of GlnZ have been explored in a number of previous studies (50,51), and many of those identified previously have also been identified in the currently study (Figure S3A). However, our data additionally uncovered that GlnZ interacts with the mRNA of nac in the N-growth state, which encodes a global transcription factor and is a member of the NtrC regulon.…”
Section: Discussionmentioning
confidence: 69%
“…For example, GlnZ could have a positive regulatory effect on nac mRNA and thereby increase Nac proteins levels in N-bacteria to repress the transcription of sucA . As sucA encodes a subunit of 2-oxoglutarate dehydrogenase enzyme, the cooperative action of GlnZ and Nac could allow efficient balancing of carbon and nitrogen metabolism at the onset of N starvation (50,51). Further, our analysis of RNA-RNA chimeras involving NtrC activated genes from different stages of N starvation in E. coli underscores that post-transcriptional regulation is clearly an important, yet relatively underexplored, facet of the adaptive response to N starvation in E. coli (Figure S3B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is exemplified by GlnZ whose expression is activated by NtrC and is thus a member of the NtrC regulon. The regulatory targets of GlnZ have been explored in a number of previous studies ( 53 , 54 ), and many of those identified previously have also been identified in the currently study ( Supplementary Figure S3A ). However, our data additionally uncovered that GlnZ interacts with the mRNA of nac in the N- growth state, which encodes a global transcription factor and is a member of the NtrC regulon.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, the extent to which post-transcriptional regulation contributes to the adaptive response to N starvation is not fully understood. Recently, the sRNA GlnZ was shown to promote cell survival by regulating genes linked to N and carbon flux in N starved E. coli in an Hfq-dependent manner ( 53 , 54 ). In MS2-affinity purification and RNA sequencing (MAPS) experiments using GlnZ as bait, conducted in short-term N-starved E. coli (i.e.…”
Section: Resultsmentioning
confidence: 99%